2017
DOI: 10.3892/or.2017.5895
|View full text |Cite
|
Sign up to set email alerts
|

Pomolic acid induces apoptosis and inhibits multidrug resistance protein MRP1 and migration in glioblastoma cells

Abstract: Glioblastoma (GBM), the most aggressive of primary brain tumors, determine short survival and poor quality of life. Therapies used for its treatment are not effective and chemotherapy failure is partially due to multidrug resistance (MDR) mechanisms present in the tumor cells. New therapeutic strategies are needed in order to improve survival in GBM. The present study investigated the activity of the pentacyclic triterpene pomolic acid (PA) in GBM. Pomolic acid decreased the viability and induced apoptosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…PA increased the total apoptotic dead percentage from 19.40 % at 10 μM concentration to 72.40 % at 20 μM while TA risen from 27.56 % to 29.11 % at the same concentrations. This result is consistent with the literature since the apoptosis-inducing effect of PA and TA was previously reported in glioblastoma cells (Guimaraes et al, 2017) and vascular smooth muscle cells (Fogo et al, 2003).…”
Section: Apoptosis-inducing Effect In Macrophage Cells By Pomolic Andsupporting
confidence: 94%
“…PA increased the total apoptotic dead percentage from 19.40 % at 10 μM concentration to 72.40 % at 20 μM while TA risen from 27.56 % to 29.11 % at the same concentrations. This result is consistent with the literature since the apoptosis-inducing effect of PA and TA was previously reported in glioblastoma cells (Guimaraes et al, 2017) and vascular smooth muscle cells (Fogo et al, 2003).…”
Section: Apoptosis-inducing Effect In Macrophage Cells By Pomolic Andsupporting
confidence: 94%
“…The antitumor activity of triterpenes in several cancer lineages, including PC, is well known (13,15,21,33,34). Similar to other triterpenes, PA shows potent antitumor activity, reducing the viability and inducing apoptosis of different tumor cell lines (17,35,36) including cancer cells presenting different MDR mechanisms (18). Our results (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Specifically, PA treatment increased caspase-3 and -9 activity and ROS production while decreasing the mitochondrial transmembrane potential in a time-dependent manner; the results indicate that the PA pro-apoptotic mechanism of action involves the activation of the intrinsic pathway in the presence of increased ROS production. The inhibition of glioblastoma cell migration in the same study was revealed to be a consequence of PA’s ability to down-modulate the activity of MRP1/ABCC1, two important transporter proteins involved in tumor drug resistance and progression [ 224 ]. Martins et al investigated the molecular mechanisms behind the antitumor activity of PA in parental PC3 and docetaxel-resistant prostate cancer PC3R cell lines and revealed a decrease in cell viability accompanied by cell apoptosis.…”
Section: Pomolic Acidmentioning
confidence: 99%